1996
DOI: 10.1007/bf02505815
|View full text |Cite
|
Sign up to set email alerts
|

Extralobar sequestration with unusual arterial supply and venous drainage

Abstract: We present a case of extralobar pulmonary sequestration between the left lower lobe and diaphragm with an unusual arterial blood supply and venous drainage. Angiography revealed a large systemic artery arising from the left subclavian artery. The venous return paralleled this anomalous artery and drained into the left subclavian vein. This case illustrates the wide anatomic variability of such complex bronchovascular anomalies. Careful preoperative evaluation of both the arterial supply and venous drainage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Atypical systemic venous drainage occurs less frequently than atypical arterial supply in congenital lung lesions, as the majority of intralobar BPS show normal venous drainage via pulmonary veins. Nevertheless, systemic venous drainage may also be found in IBPS ( 6 ). Supra-diaphragmatic systemic venous drainage in congenital lung lesions seems to be frequently connected to the azygos and less commonly to the hemiazygos system ( 4 , 7 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypical systemic venous drainage occurs less frequently than atypical arterial supply in congenital lung lesions, as the majority of intralobar BPS show normal venous drainage via pulmonary veins. Nevertheless, systemic venous drainage may also be found in IBPS ( 6 ). Supra-diaphragmatic systemic venous drainage in congenital lung lesions seems to be frequently connected to the azygos and less commonly to the hemiazygos system ( 4 , 7 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supra-diaphragmatic systemic venous drainage in congenital lung lesions seems to be frequently connected to the azygos and less commonly to the hemiazygos system ( 4 , 7 9 ). Supra-diaphragmatic systemic venous return into the subclavian vein ( 6 ) and intercostal vein ( 9 ) has been described. Infra-diaphragmatic systemic venous drainage, as in one of our patients with EBPS, has been found via portal vein ( 9 , 14 17 ), inferior caval vein, splenic and suprarenal vein.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sauvanet and colleagues reported that the arteriography was diagnostic in only 28 of 40 cases [ 6 ]. Magnetic resonance angiography is useful in delineating the vascular anatomy of the sequestration [ 7 ]. Except arteriography, pulmonary angiography, magnetic resonance imaging; computed tomographic scanning, bronchography, and ultrasonographies have all been used in selected cases for preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…While the systemic collateral artery arises from the subclavian artery through the patent ductus arteriosus in patient 11, this may be the facsimile of the systemic pulmonary artery described by Cucci et al, 11 as in the cases of``absence of a primitive division of the pulmonary trunk'' due to defective septation of the truncus at Streeter Horizons XV±XVII (a 30±36-day embryo). 14,15 In the English-language literature, we found cases of pulmonary sequestration with systemic arterialization from the subclavian or intercostal artery, 16,17 which are similar in course to those of type III MAPCAs. Autopsy in patient 11 with isolated levocardia, bronchus inversus, visceroatrial inversus, common atrium, common atrioventricular valve, single ventricle, solitary outlet of the aorta, PDA, and pulmonary atresia showed a systemic feeding artery arising from the left subclavian artery via a PDA to the right lower lobe of the bilobed lung without bronchopulmonary airway sequestration.…”
Section: Cardiovascular Hypothesismentioning
confidence: 94%